Determinants of Stock Market Investment Decisions Among Youth Investors in Pokhara Metropolis - Poudel , Hem Kanta; Ranabhat, Deepesh Ranabhat; Palikhe , Srijan Man; Ranabhat , Mala (Khwopa Journal, 2025)
Stock markets are essential for a country’s economic growth, providing a platform for businesses to raise capital and individuals to invest in their savings. In Nepal, the stock market has grown over the years, primarily driven by the activities of the Nepal Stock Exchange (NEPSE), which is the country’s sole stock exchange. This study examines the determinants of stock market investment decisions among youth investors in the Pokhara metropolis, focusing on five factors: investors’ education, demographic factors, investors’ experience, financial literacy, and source of information. A quantitative research approach with descriptive and analytical designs was employed. Primary data were collected from 200 youth investors of the stock market in Pokhara Metropolis using a Google form questionnaire survey. The study utilized correlation and regression analyses to evaluate relationships and the impact of variables. The finding revealed that investment decisions are significantly influenced by financial literacy (ẞ = 0.463), education (ẞ = 0.165), and source of information (ẞ = 0.216) with p-value less than 0.05, while demographics and experience were not significant predictors. This study concludes that the youth investors in Pokhara metropolis should focus on financial literacy for stock market investment, increase the education level and reliable sources of information related to the stock market, and make it a more secure investment. This study is limited to the youth investors in stock market investment only. However, these findings provide valuable insights for young investors in the stock market to make informed investment decisions and for policymakers to promote financial inclusion and support the development of the nation’s economy. To have an additional complete reflection, forthcoming research would investigate behavioral, and technological aspects influencing new investment choices in the stock market across various geographic areas of Nepal.